Inspeção de feixes tubulares de trocadores de calor - Ricardo Schayer Sabino (2008)
Decisions making related to the physical conditions of tubular bundles of heat exchangers involves an important subjective aspect due to the intrinsic difficulty of inspection of those components promoted by the complex lay-out of its tubes and consequent lack of visual access. Therefore, it is not unusual to occur failure of those equipments during the campaign of a process plant. This paper presents a critical analysis of common techniques used to represent and evaluate tubularbundles based on non-destructive examinations. The results of the Department of Equipment Inspection´s analyses of 30 heat exchangers, with tubes of carbon steel and subjected to IRIS tests, has been compared to results obtained by use of statistical models based on normal, Student, Weibull and smallest extreme value distributions. The parameters of those models have been estimated by the maximum likelihood method and the goodness of fit for each model has beenevaluated by the Anderson-Darling test. Hypothesis tests were developed for the evaluation of the physical conditions of the bundles and for the need of replacement of their tubes. The results demonstrate that it is usual to undersize samples, the Normal model can be used with restrictions, the Student model did not detect the bundles with low availability and shall not be used for this kind of analysis, and the Weibull and smallest extreme value models presented more conservativeresults than the Department of Equipment Inspection´s analyses.